Energy Conservation Awareness and Behaviour among Students: Faculty of Medicine Sabratha as a Case Study - Abduanaser A Ali Ezhani; Hamza Mohamed Flafel; Asma Ayad Makhibish; Alaa Albasheer Algharabli (African Journal of Advanced Pure and Applied Sciences, 2022)
Libya facing high consumption and production patterns that do not achieve economic sustainability. Universities have high-energy waste due to a lack of energy awareness and inefficient use of energy among students. Energy education of the younger generation who are the future decision-makers. Energy-saving efforts need to be taken to reduce the negative effects of higher energy consumption and greenhouse gas (GHG) emissions have continued to rise. Therefore, without knowing the level of energy awareness and energy-use behaviour, it is difficult to plan and provide a better energy conservation program. The purpose of this research is to identify the level of energy-saving behaviour- awareness and to determine the main important factors that contribute to energy saving among students in faculty of medicine sabratha. Data were gathered using a survey questionnaire on approximately 80 full-time students. The results indicated that students have a low level of energy awareness and behaviour. In addition, results shows that increasing the level of energy awareness enhances energy-use behaviour for respondents. For achieving the third objective of the study (new electricity appliances & social media) have the top of the important factors contribute to energy saving. Energy saving is one of the most necessary options towards the reduction of energy consumption.